2017
DOI: 10.1016/j.prnil.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma enables selection and monitoring of active surveillance candidates using nuclear magnetic resonance-based metabolomics: A preliminary investigation

Abstract: BackgroundDiagnosis and monitoring of localized prostate cancer requires discovery and validation of noninvasive biomarkers. Nuclear magnetic resonance (NMR)-based metabolomics of seminal plasma reportedly improves diagnostic accuracy, but requires validation in a high-risk clinical cohort.Materials and methodsSeminal plasma samples of 151 men being investigated for prostate cancer were analyzed with 1H-NMR spectroscopy. After adjustment for buffer (add-to-subtract) and endogenous enzyme influence on metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…Several studies on small cohorts have searched for PCa biomarkers in semen or expressed prostatic secretions, showing decreased citrate levels in PCa compared with healthy controls . This could however not be confirmed in a larger study performing metabolic profiling of seminal plasma from 151 high‐risk participants, of which 98 had proven PCa . In this cohort, citrate was not a predictor for PCa, and the significant metabolites choline and leucine did not improve diagnosis compared with PSA measurements.…”
Section: Cancer Detection and Diagnosismentioning
confidence: 70%
“…Several studies on small cohorts have searched for PCa biomarkers in semen or expressed prostatic secretions, showing decreased citrate levels in PCa compared with healthy controls . This could however not be confirmed in a larger study performing metabolic profiling of seminal plasma from 151 high‐risk participants, of which 98 had proven PCa . In this cohort, citrate was not a predictor for PCa, and the significant metabolites choline and leucine did not improve diagnosis compared with PSA measurements.…”
Section: Cancer Detection and Diagnosismentioning
confidence: 70%
“…Roberts et al conducted a study using seminal plasma for selection and monitoring of active surveillance candidates using NMR based metabolomics [63]. One hundred fifty-one men who were investigated for elevated PSA and/or abnormal DRE were included in the prospective cohort study.…”
Section: Resultsmentioning
confidence: 99%
“…PCa is a disease of great interest from a metabolomics perspective. A number of studies, focused on the characterization of the specific PCa metabolic phenotype using different experimental approaches, have been reported recently [37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61]. These studies have shown that healthy prostate cells are characterized by a decreased citrate oxidation and metabolism within the tricarboxylic acid (TCA) cycle, resulting in citrate accumulation [62] and the reliance on glucose oxidation for energy production [63].…”
Section: Metabolomics and Pcamentioning
confidence: 99%
“…This study revealed that concentrations of citrate, myo-inositol, and spermine were inversely correlated with PCa risk (AUC values of 0.89, 0.87 and 0.79, respectively). However, in a more recent study attempting to validate the role of these metabolites as biomarkers for assessing PCa risk, Roberts et al found that citrate, spermine, and myo-inositol had minimal predictive ability when analyzing seminal fluid samples [61]. Therefore, further studies using larger cohorts will be required to confirm the utility of seminal fluid and EPS derived biomarkers for PCa diagnosis and prognosis.…”
Section: Pca Metabolic Biomarkers In Biofluidsmentioning
confidence: 99%